ANALISIS KETERKAITAN FINANCIAL S ANALISIS KETERKAITAN FINANCIAL SHENANIGANS PADA PERUSAHAAN PT BANK BUKOPIN TBK - shandy -; Natalis Christian; Reny -; Greece Agustin; Kelly Paticia (JURNAL AKUNTANSI, 2021)
This study aims to examine what financial shenanigans have been violated by one of the IDX companies in Indonesia, namely PT. Bank Bukopin Tbk from 2016 to 2020. Cases of manipulation or falsification of corporate financial report data often occur in various companies without knowing the reputation or scale of the company. Manipulation or falsification of financial report data is carried out with the aim of the company being able to attract investors to believe in the company's transparency. Financial shenanigans is a theory that provides an explanation of how to detect fraud that may occur in a company's financial statements. This study also explains the theories of financial shenanigans 1 to 7 from books or other sources related to the topic of discussion. The results of this study indicate that that PT. Bank Bukopin is suspected of manipulating data presented in financial reports such as overstates. Relation to financial shenanigans, namely recording fictitious income, shifting current costs to the next period and acknowledging the existence of counterfeit income.